Leadership roles in community development in Malaysia. - Mohamad , Madinah; Silong, Abu Daud (The Journal of Global Business Management, 2010)
What are the leadership roles in community development in Malaysia? Initial research findings based on a survey and focus group interviews of committee members of Neighborhood Associations in Malaysia identified various leadership roles that relate to community development. This research is an extension of those studies using the in-depth interviews of eight Chairmen of the Neighborhood Associations in the state of Penang, Malaysia. Mintzberg's and Yukl's leadership roles were used as a theoretical framework for the study. The terms leadership and community development were also reviewed. Based on the findings of the study, the leadership roles and issues related to community leaders in Malaysia are identified and discussed in relation to community development in the country. They include the leadership roles such as being a leader in a multi-racial team, change agent, problem-solver, manager, communicator, negotiator and resource-linker. Some implications and recommendations for leadership development are proposed